Bubbling of Ferrofluid Droplets via Coupled Magnetic and Sound Fields - Kangqi Liu; Yuan Gao; Xiuxing Tang; Yongjian Zhang; Xiaojun Bai; Duyang Zang (Advanced Materials Interfaces, 2023)
Abstract Bubbles play essential roles in many natural and industrial processes because of the unique effects of their films on heat–mass transfer and their soft confined geometry for interfacial assembly or phase transitions. Here, a technique for noncontact bubbling via coupling of sound and magnetic fields in acoustic levitation is reported. An acoustically levitated ferrofluid droplet can be transformed into a closed bubble in a controlled manner. It has been found that the magnetic field pulls the flattened ferrofluid film downward, and making it deviate from its initial levitation position determined by the balance between acoustic radiation force and gravity. This results in variation in acoustic radiation pressure on the film surface and generates an upwards torque on the levitated film, leading to buckling and subsequent bubble transition via acoustic resonance. Moreover, the levitated ferrofluid bubble can remain unburst in the sound field for minutes to enable its complete evaporation; thus, solid hollow shells form. This work provides insight for understanding the coupled effect of sound and magnetic fields on ferrofluid drops and sheds light on evaporation‐driven self‐assembly of ferrofluid particles into shell structures